Technology and Marketing - Jafar Ojra (Advances in Marketing, Customer Relationship Management, and E-Services, 2022)
Digital technologies have tremendously evolved and become a part of daily life. This constant evolution constitutes a major determinant of how consumers and organisations engage. For consumers, the evolvement intensifies their socialising capacity with customers of like mind, voice their dissatisfaction, and explore alternative options. Marketers leverage the digital evolvement to engage with customers, acquire marketing intelligence, and exploit customers’ purchase behaviour emotions. Recognising the growing digital technologies trend and importance to marketing, this chapter highlights the need for more effort towards enhancing the technology-marketing interface. Given that movement restriction-induced consequences of COVID-19 have intensified the paradigm shift from physical to virtual marketing, this chapter forwards a theoretical framing that takes a technology-marketing viewpoint that focuses on customer engagement and ensuring implementation processes for effectively managing associated challenges. Finally, recommendations are offered and future research directions flagged.